F Price Fluctuations of Fresh Fruit Bunches of Oil Palm at the Loading Ramp in Janju Village, Tanah Grogot Subdistrict (Case Study Loading Ramp of Alam Tuah): Price Fluctuations of Fresh Fruit Bunches of Oil Palm - Juraemi, Juraemi; Tetty Wijayanti; Apri Josua Ruhut Manurung (International Journal of Technology and Education Research, 2024)
The price of Fresh Fruit Bunches (FFB) of oil palm is the price given to farmers who sell their FFB to Palm Oil Processing Plants (POPP), middlemen, and loading ramps. Alam Tuah Loading Ramp is one of the marketing entities similar to middlemen. Alam Tuah Loading Ramp sets the price of oil palm FFB, and there is a phenomenon of price fluctuations. This study aims to address the phenomenon of price fluctuations at Alam Tuah Loading Ramp, specifically to determine the conformity of the prevailing FFB prices with those set by the government, the extent of price fluctuations, and the factors influencing the price determination of FFB at Alam Tuah Loading Ramp. The study was conducted at Alam Tuah Loading Ramp, Janju Tanah Grogot Village Subdistrict, from January to March 2024. This research is a qualitative descriptive study. Data and information were collected using questionnaires and interviews. The data were analyzed using coefficient of variation (CV) analysis to determine the extent of price fluctuations. The study reveals that the price of oil palm FFB at Alam Tuah Loading Ramp does not align with the government-set price and is lower than the government-determined price. The analysis results show that the price fluctuation of FFB at Alam Tuah Loading Ramp reached 35% in 2022, 11% in 2023, and 27% over the period from 2022 to 2023. There was a higher fluctuation in 2022 compared to 2023 at Alam Tuah Loading Ramp. The price of oil palm FFB at Alam Tuah Loading Ramp is determined based on the price of FFB at POPP CBSS, operational costs, and profit margins.